BUDGET REVENUES AND TAX FIELDS (Conferencea, 2023)
The article contains scientific proposals and practical recommendations to support the ongoing reforms in Uzbekistan to ensure the sustainability of local budget revenues, the economic significance of local budget revenues, mechanisms for regulating local budget revenues.